PERENCANAAN STRATEGIS SISTEM INFORMASI PADA CV. REJEKI RAYA SEJAHTERA MENGGUNAKAN METODE WARD AND PEPPARD - Michella Valery; Vivian Vivian; Agnes Monica; Nicholas Monica; Mulyati Mulyati (Jurnal Riset Sistem Informasi, 2026)
The alignment of information systems with business needs plays an important role in improving organizational operational effectiveness. CV Rejeki Raya Sejahtera faces challenges because its information systems have not been strategically planned, resulting in limited support for achieving business objectives. This study aims to develop an information systems strategic plan that aligns with the company’s conditions and business needs. The study employs the Ward and Peppard method using a qualitative descriptive approach. Data were collected through interviews and observations, then analyzed using internal and external environmental analysis and information systems mapping with the McFarlan Strategic Grid. The results indicate that existing information systems are still focused on operational activities and have not yet supported business strategy. The contribution of this study is a structured application portfolio and IS/IT development recommendations, which are expected to improve business process effectiveness and support managerial decision making in a sustainable manner for organizational contexts.